PERSEPSI DAN SIKAP MASYARAKAT TERHADAP KONSERVASI HUTAN MANTOBE DI DESA SONDAKEN, MINAHASA SELATAN - Opriani Devi Tangilomban; Wawan Nurmawan; Lyndon R. J, Pangemanan (Universitas Sam Ratulangi, 2021)
Abstract Mangrove forest is generally a coastal vegetation community tropical climate, which is dominated by several types of trees that are able to grow and thrive in muddy coastal tidal areas and for coastal communities. The purpose of this study was to examine the level of community perception and attitude towards mangrove forest conservation in Sondaken Village, Tatapaan District, South Minahasa Regency. The method used in this study using interviews and observation. The results showed that the community's perception of mangrove forest conservation in Sondaken Village was quite good to very very good, while the attitude was not good to very good. Keywords: Mangrove forest, community perception and attitude, Sondaken Village Desa